IJIMAI Editor's Note - Vol. 4 Issue 3 - García-Díaz, Vicente (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
The Internet of Things is the networks of physical devices, embedded with electronics, software, sensors, actuators and security and connectivity mechanisms that enables them to collect and exchange data. It is a very important research topic nowadays in which many scientific papers are focusing on its bases. This Special Issue tries to show some of the latest researches related to IoT with special emphasis on the basic components of IoT, some of the major applications in which researchers and practitioners are working and especially in aspects related to security, one of the main areas of research related to IoT, with a special emphasis on cloud-based systems. Next, I present a summary of the works that are included in this special issue.
Keywords: internet of things; editors note; cloud computing; IJIMAI